Pemberdayaan Masyarakat Melalui Program KKN Society 5.0 di Desa Planjan Kecamatan Saptosari Kabupaten Gunungkidul - Latumahina, Bill Samuel; Nugrahanto, Cornelius Septian; Daniel, Daniel; Ermawati, Ermawati; Damanik, Justin Gamaliel; Christiyanto, Laurensius Erdin; Nurmawan, Mardatungga; Angelita, Maya; Mulyono, Romi Kurniawan Agni; Kirana, Stephani Nindya; Widiastiani, Nindry Sulistya (Jurnal Atma Inovasia, 2021)
Community empowerment activities in the Covid-19 pandemic era were conducted by students through Kuliah Kerja Nyata (KKN) Society 5.0 or KKN 78 which was conducted without field landing. This activity aims to increase students' empathy towards the villagers with various programs to develop potential and solve problems in the place. Group 38 was stationed in Planjan Village, Saptosari Sub-District, Gunungkidul, D.I. Yogyakarta. The programs carried out by the group 38 are KKN Village Potential and KKN Pocketbook. The resulting program is (1) ebook and video  development of planjan village potential related to gejog lesung arts, development of Omang Lake as a tourist attraction and empowerment of copper craftsmen; (2) ebooks and videos of family medicinal plants (TOGA). Each member of the group also produces individual programs titled KKN Counseling, KKN Field of Science and KKN Entrepreneurship. The devotion program is expected to encourage student participation in serving others and assist in the development of Planjan Village.